ENVIRONMENT AND SUSTAINABLE URBAN DEVELOPMENT - Johri, Deepa (International Journal of Research -GRANTHAALAYAH, 2015)
Human beings interact both with the social world and nature for its survival. Natural resources and Economic base along with Technology are required for the continual improvement of life style and living standard. Up till now the development was achieved by over exploitation of resources which has damaged the environment and we are facing its consequences. A major cause of this situation is the fast urban growth. India is witnessing an unprecndental rise in urbanization in last two decade. But Indian cities are not able to manage the increasing population because of poor urban management and resource constraints. These cities and their residents are fighting again population, lack of safe drinking water, scarcity of electricity and other basic amenities. Population and degradation of social & physical environment is a major issue in most of the cities in India, but at the same time cities are paving a way for a new cultural & economic development. The present study analysis urban and development in India and its impact on environment growth. Urbanization and sustainable development can be achieved if population growth and management of resources are catered properly, unfortunately it is not the scene of Indian urban growth. Thirteen out of twenty most polluted cities of world are Indian cities. We need an immediate control and overview of present trend of urbanization. This research paper is an attempt to identity the major issues of environment in class II &III cities of MP and to explore the path for sustainable development.